2001
DOI: 10.1097/00004770-200108000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Response of Human Pulpal Tissue to Orthodontic Extrusive Applications

Abstract: The aim of this study was to investigate histologically the human pulp response to orthodontic extrusive force applications. In group 1, 20 teeth were extruded with the use of a fixed sectional orthodontic appliance. In group 2, 20 teeth were extruded by means of 1/4-inch 4.5-oz elastics. The test periods were 10 and 40 days. None of the teeth in the groups showed any inflammatory reactions or reparative dentin formation at the test periods. Five teeth from the elastics group and two teeth from the sectional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 10 publications
1
26
4
Order By: Relevance
“…34 Previous studies demonstrated the influence of mechanical stress in the differentiation of DPSCs, although the results are controversial. [18][19][20] Han et al revealed that continuous cyclic mechanical tension for 4-10 days increased proliferation and collagen/osteopontin expression in DPSCs. 35 Yu et al showed DPSCs increased odontogenic differentiation, early in vitro mineralization, with slightly disrupted survival by hydrostatic pressure for 2 h. 15 Cai et al indicated that a 6-h uni-axially cyclic tensile stretch inhibited osteogenic differentiation of DPSCs.…”
Section: Stretch Increases Proliferation Without Differentiation In Dmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Previous studies demonstrated the influence of mechanical stress in the differentiation of DPSCs, although the results are controversial. [18][19][20] Han et al revealed that continuous cyclic mechanical tension for 4-10 days increased proliferation and collagen/osteopontin expression in DPSCs. 35 Yu et al showed DPSCs increased odontogenic differentiation, early in vitro mineralization, with slightly disrupted survival by hydrostatic pressure for 2 h. 15 Cai et al indicated that a 6-h uni-axially cyclic tensile stretch inhibited osteogenic differentiation of DPSCs.…”
Section: Stretch Increases Proliferation Without Differentiation In Dmentioning
confidence: 99%
“…Some demonstrated the promotion of odontoblastic differentiation by mechanical stress in human DPSCs, 18,19 whereas others reported that mechanical stress had no significant effect on the differentiation of human dental pulp. 20 These results suggest that the response to mechanical stress differs by the type and the duration of mechanical force. Furthermore, the intracellular signaling by mechanical force was poorly investigated in DPSCs.…”
mentioning
confidence: 91%
“…This finding significantly expanded our expectations to explain the formation of dental pulp calcification, of which the etiology until now was ambiguous. [19][20][21][22] As far as we know today, pulp calcification is a type of chronic regressive degeneration of the pulp tissue; however, what leads to this devolution remains unclear. Dystrophic calcification is found to be of a variable degree, and this might originate from the impairment of the host cells.…”
Section: Introductionmentioning
confidence: 99%
“…Most of researchers 1,3,7,9 stated that orthodontic force presents a negative impact on pulp tissue, whereas other researchers said that orthodontic force creates no specific impact on pulp tissue. 4,10,19 The result research on pulp tissue reaction towards orthodontic force, found histological tissue changes on almost all observed cases. The most frequent changes discovered were damages on odontoblast layer.…”
Section: Discussionmentioning
confidence: 92%
“…disrupted blood circulation, and necrosis. 4 On the contrary, other researchers testified that orthodontic forces had no prolonged significant negative effect on pulp. 3 Numerous researches on pulp tissue changes caused by orthodontic forces have been performed, among others are: pulp tissue respiration rate, 1 pulp angiogenesis, 2 pulp tissue response due to dental extrusion, 4 aspartate aminotransferase 3,5 and alkaline phosphatase 6,7 enzyme activities and pulp micro vascular response.…”
Section: Introductionmentioning
confidence: 98%